Translational Medicine: Exercise Physiology Applied to Metabolic Myopathies. Issue 11 (November 2019) - GRASSI, BRUNO; PORCELLI, SIMONE; MARZORATI, MAURO
ABSTRACT: N/A: The relevance of translational medicine (bringing basic science methods "to the bed of patients") is universally recognized. Too often, however, the tools to be applied translationally are thought to derive only from the "-omics" (genomics, proteomics, transcriptomics, metabolomics, etc.) world. The failures of this "reductionist" approach are widely recognized. In the review, we discuss studies demonstrating that scientifically sound mechanistic insights into diseases, relevant both in terms of basic science and clinically, and very well suited to be utilized within a translational medicine approach, can be obtained from the established field of exercise physiology. Methods originally aimed toward basic physiological mechanisms, and applied for the functional evaluation of athletes and sport performance, can have a valuable translational application in patients with metabolic myopathies; such as myophosphorylase deficiency (McArdle disease) or mitochondrial myopathies, diseases which share the common denominator of an impaired skeletal muscle oxidative metabolism. Several variables can yield pathophysiological insights, can identify and quantify the metabolic impairment and the effects on exercise tolerance (one of the main determinants of the patients' clinical picture and quality of life), and can offer diagnostic clues: the impaired capacity of O2 extraction by skeletal muscle, evaluated by near-infrared spectroscopy; the "exaggerated" cardiovascular response to exercise; the slower speed of adjustment of oxidative metabolism during metabolic transitions; the "slow component" of pulmonary O2 uptake kinetics and the associated reduced efficiency and fatigue; the impaired intramuscular matching between O2 delivery and O2 utilization. The proposed methods are noninvasive, and therefore facilitate repeated or serial evaluations. They provide support for a simple message: physiology and physiological research remain the essential link between genes, molecules, and clinical care.